2022
DOI: 10.1111/jnp.12293
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery vividness and symptom severity in Parkinson's disease

Abstract: Motor imagery (MI), the mental simulation of movement in the absence of overt motor output, has demonstrated potential as a technique to support rehabilitation of movement in neurological conditions such as Parkinson's disease (PD).Existing evidence suggests that MI is largely preserved in PD, but previous studies have typically examined global measures of MI and have not considered the potential impact of individual differences in symptom presentation on MI. The present study investigated the influence of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Music-evoked motor imagery was reported as being at least moderately vivid by the majority of PwP. Visual motor imagery was rated as more vivid than kinesthetic motor imagery, revealing a similar pattern to ratings of general (i.e., not music-evoked) motor imagery as measured by the KVIQ in PwP (Bek et al, 2022b;Readman et al, 2023) and in the general population (e.g., Malouin et al, 2007). This finding also provides some face validity for our novel rating of music-evoked motor imagery, suggesting that participants were able to rate their experiences of this type of imagery in a similar way to general motor imagery.…”
Section: Motor Imagery and Musicmentioning
confidence: 70%
“…Music-evoked motor imagery was reported as being at least moderately vivid by the majority of PwP. Visual motor imagery was rated as more vivid than kinesthetic motor imagery, revealing a similar pattern to ratings of general (i.e., not music-evoked) motor imagery as measured by the KVIQ in PwP (Bek et al, 2022b;Readman et al, 2023) and in the general population (e.g., Malouin et al, 2007). This finding also provides some face validity for our novel rating of music-evoked motor imagery, suggesting that participants were able to rate their experiences of this type of imagery in a similar way to general motor imagery.…”
Section: Motor Imagery and Musicmentioning
confidence: 70%
“…In contrast, other studies have found differences in these tasks in people with PD, secondary to alterations in fronto-striatal motor systems and parietal lobes, which are involved in integrating visuospatial information and imagery [15]. Also, factors such as the degree of severity of left side bradykinesia have been found to correlate with the vividness of MI, suggesting that specific motor symptoms of PD may alter these abilities [16].…”
Section: Introductionmentioning
confidence: 91%
“…The present study did not find moderate or strong correlations between the ability to create MI and upper limb motor function, gait and balance, suggesting that people with PD retain movement representation, but execution components hinder functionality. Also, it is worth mentioning that there are large individual differences in MI even in the general population and these might also explain a null effect at this point, suggesting that MI might not be suitable for people unable to create vivid images [16,48].…”
Section: Functional Implications and Relationship With Adl And Qolmentioning
confidence: 99%
“…The earliest signs of PD include tremors, stiffness, and slow movement. As the disease progresses, individuals may experience difficulty with balance, coordination, and fine motor skills [119]. In addition to motor symptoms, PD can cause non-motor symptoms such as depression, anxiety, and sleep disturbances.…”
Section: Neuroimaging Studies On Neurological Disorders Such As Ad An...mentioning
confidence: 99%